NILAI TAMBAH KERIPIK PISANG PADA INDUSTRI RUMAH TANGGA IBU DEWI (Studi Kasus Kecamatan Malalayang) - Wahyudi ., Mokodongan; Juliana R. Mandei; Joachim N.K. Dumais (AGRI-SOSIOEKONOMI, 2017)
This study aims to determine the amount of: (1) the cost per one time production, (2) revenue and income per one time production (3) added value from the banana processing business into banana chips. This research was conducted in Kecamatan Malalayang. Data collection begins at the end of February to March 2017. Data collection methods are conducted using primary data. Primary data was obtained through interviews based on a prepared list of questions, as well as on-site observations. The data collected involves: The variable cost is the amount of value influenced by the amount of production of banana chips is the cost of raw materials (bananas) and the cost of fuel (kerosene, LPG gas), Fixed costs consist of: depreciation cost of equipment and construction depreciation or cost other beyond the variable cost. Depreciation is the cost of depreciation per year, ie stove, knife, spoon of fryers, chopper, scales, and trays per year. Additives material are ingredients other than the main ingredients needed in the production process ie cooking oil, sugar, salt, egg yolk, and wrapping plastic. The total cost is all costs incurred in the production of bananas into banana chips. Methods of data analysis conducted in this study are: (1) calculate the total cost per one time production, (2) calculate the business profits processing banana fruit into banana chips per one time production with the formula Ï€ = TR - TC. (3) Calculating the added value of the banana processing business into banana chips. The results showed that (1) The amount of cost the banana Dewi chips per production is Rp. 164.000, - with details of banana raw material Rp. 25.000, - and auxiliary materials, among others, cooking oil, sugar, salt, egg yolks cendrawasih, plastic wrapping, and gas Rp. 139.000, -. (2) Large income and income per one time banana banana chips production is 20 packs per one time production with selling price Rp. 20.000, - so the revenue of Dewi banana chips is 400,000, - and (3) the amount of added value from the processing of banana into Dewi banana chips is Rp. 232.555,48 and for the value added to the raw material of banana chips, 232.555.48 divided by 100 bananas the result is 2,325,55, meaning that each banana that is processed into banana chips can give the addition of value of 2,325,55.